Forage and pasture legume biodiversity in the semi-arid areas of West Central Morocco - El Mzouri E.; Thami Alami I. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
Morocco is one of the Mediterranean countries known for their native pasture legume biodiversity. However, successive droughts, continuous overgrazing, and some cultural practices such as weeding have contributed to the increase of erosion of the genetic resources of native pasture legumes and there are only few efforts made to save in situ seed production of these species. The objectives of this study were to assess the actual situation of the pasture legume biodiversity in cropland of semi-arid and arid areas in western Morocco and to examine their distribution according to rainfall and soil pH. The germplasm collection covered a total distance of 1000 km with high variability in rainfall and soil conditions. Ten native forage and pasture legume genera were identified. The dominant genera were Medicago, Trifolium, and Astragalus with 10, 7 and 4 species, respectively. The total number of species identified varied significantly between collection sites. Rainfall and soil pH affected legumes presence and distribution.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)